X-ray photoelectron spectroscopy study of the passive films formed on thermally sprayed and wrought Inconel 625 - Bakare, M.S.; Voisey, K.T.; Roe, M.J.; McCartney, D.G. (Elsevier, 2010)
There is a well known performance gap in corrosion resistance between thermally sprayed corrosion resistant coatings and the equivalent bulk materials. Interconnected porosity has an important and well known effect, however there are additional relevant microstructural effects. Previous work has shown that a compositional difference exists between the regions of resolidified and non-melted material that exist in the as-sprayed coatings. The resolidified regions are depleted in oxide forming elements due to formation of oxides during coating deposition. Formation of galvanic cells between these different regions is believed to decrease the corrosion resistance of the coating. In order to increase understanding of the details of this effect, this work uses X-ray photoelectron spectroscopy (XPS) to study the passive films formed on thermally sprayed coatings (HVOF) and bulk Inconel 625, a commercially available corrosion resistant Ni-Cr-Mo-Nb alloy. Passive films produced by potentiodynamic scanning to 400mV in 0.5M sulphuric acid were compared with air formed films. The poorer corrosion performance of the thermally sprayed coatings was attributed to Ni(OH)2, which forms a loose, non-adherent and therefore non-protective film. The good corrosion resistance of wrought Inconel 625 is due to formation of Cr, Mo and Nb oxides. Keywords: